Pt-based dehydrogenation catalyst and its application
By dispersing the active component Pt of the Pt-based dehydrogenation catalyst on the outer layer of the catalyst, the problem that the catalyst is not easily burned out completely during the burning and regeneration process is solved, and the complete regeneration of the catalyst and the recovery of reaction performance are achieved, and production efficiency and safety are improved.
Patent Information
- Application Number
- CN202111675656.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-12-31
AI Technical Summary
During the burning and regeneration process of existing Pt-based dehydrogenation catalysts, the carbon deposits in the center or core of the catalyst are not easily completely burned away, resulting in catalyst damage, serious dust, decreased reaction performance, shortened construction cycle, affecting production efficiency and safe operation.
By using spherical θ-alumina as the support, the active component Pt is completely scattered in the outer layer of the catalyst to form spherical catalyst particles, and the thickness of the shell layer is 10-90% of the radius of spherical catalyst particles to ensure that coke is only generated in the outer layer of the catalyst and not in the inner core.
Complete burning and regeneration of the catalyst is achieved, reducing the chance of catalyst rupture, reducing dust and pressure drop, extending the operating cycle, and improving production efficiency and safety.
Smart Images

Figure CN116408076B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical industry, and in particular to a Pt-based dehydrogenation catalyst and application thereof. Background Art
[0002] At present, the global demand for propylene and its derivatives is growing. In order to meet the growing demand for propylene, the technology of producing propylene by dehydrogenation of propane is gaining more and more attention. Currently, the industrialized propane dehydrogenation technologies include UOP's Oleflex process and Lummus's Catofin process.
[0003] Catalysts for propane catalytic dehydrogenation are divided into platinum catalysts and chromium catalysts. The Oleflex process uses platinum catalysts, and the Catofin process uses chromium catalysts. Since the catalysts of each process involve confidential information, the information found about the catalysts is not comprehensive, but the life of the catalysts of each process is mostly about two years, but the operating cycle is different. Platinum catalysts have the remarkable characteristics of high activity, high selectivity, and low wear rate, but they are expensive, and it is difficult to stabilize the performance of traditional supported catalyst preparation methods. Chromium catalysts have good activity for the dehydrogenation of low-carbon alkanes and have relatively low requirements for impurities in the raw materials. They have strong resistance to poisoning, olefins, and oxygen-containing compounds, are cheap, and have no catalyst loss. However, this type of catalyst is prone to carbon deposition and deactivation, has poor stability, and is subject to certain restrictions due to the toxic and harmful nature of heavy metal Cr.
[0004] In Pt-based catalysts used for propane dehydrogenation, Pt atoms are dispersed on the catalyst from the inside to the outside and from the core to the outer surface. When the catalyst reacts to form coke, the carbon deposits are also dispersed on the catalyst from the inside to the outside and from the core to the outer surface. When the catalyst is coked and regenerated, the carbon deposits in the center or core of the catalyst are difficult to completely burn off, the catalyst is damaged, and the dust is serious, which leads to reduced strength of the regenerated catalyst, screen blockage, increased pressure drop, reduced reaction performance, shortened start-up cycle, and other problems, affecting production efficiency and safe operation. Summary of the invention
[0005] An object of the present invention is to provide a Pt-based dehydrogenation catalyst;
[0006] Another object of the present invention is to provide application of the Pt-based dehydrogenation catalyst.
[0007] To achieve the above-mentioned purpose, on the one hand, the present invention provides a Pt-based dehydrogenation catalyst, wherein the Pt-based dehydrogenation catalyst uses spherical θ-alumina as a carrier, the active component Pt is completely dispersed in the outer layer of the catalyst to form spherical catalyst particles, and the active component Pt forms a shell layer, and the thickness of the shell layer is 10-90% of the radius of the spherical catalyst particle.
[0008] In the present invention, the active component Pt atoms or Pt atomic clusters of the catalyst are highly dispersed and distributed in the outer layer of the catalyst, but not in the inner core of the catalyst, so that the coke after the reaction is only produced in the outer layer of the catalyst and no coke is produced in the inner core. Since the mass transfer and heat transfer efficiency of the outer layer of the catalyst is much higher than that of the inner core, the coke deposits on the catalyst are relatively easy to be completely burned off, ensuring that the reaction performance of the regenerated catalyst is fully restored. In particular, the advantages of the catalyst core of the present invention having no coke and the advantages of the lower required coking temperature can greatly reduce the probability of catalyst rupture and effectively solve the problems of large dust, large pressure drop and short operation cycle during the operation of the device.
[0009] According to some specific embodiments of the present invention, based on the total mass of the Pt-based dehydrogenation catalyst being 100%, the Pt content is 0.1-1.0 wt%.
[0010] According to some specific embodiments of the present invention, based on the total mass of the Pt-based dehydrogenation catalyst being 100%, the Pt content is 0.2-0.4 wt%.
[0011] According to some specific embodiments of the present invention, based on the total mass of the Pt-based dehydrogenation catalyst as 100%, the Pt-based dehydrogenation catalyst also contains the following percentage components: 0.05-2.0 wt% of Sn, 0-0.8 wt% of Cl, and 0.3-3.0 wt% of at least one alkali metal and / or alkaline earth metal.
[0012] The present invention has no requirement on the distribution of the above components (Sn, Cl, alkali metal and / or alkaline earth metal), and the inner core and the outer shell may be uniform, or they may be only in the outer layer (shell layer) together with Pt.
[0013] In order to solve the problem of Cl loss on the traditional propane dehydrogenation catalyst, eliminate the corrosion problem and reduce the acidity of the catalyst, the catalyst in the present invention does not contain Cl or contains only a small amount of Cl.
[0014] According to some specific embodiments of the present invention, the content of Cl is 0.1-0.8 wt %.
[0015] According to some specific embodiments of the present invention, the alkali metal is selected from one or more combinations of lithium, sodium and potassium.
[0016] According to some specific embodiments of the present invention, the alkaline earth metal is selected from magnesium or calcium.
[0017] According to some specific embodiments of the present invention, the Pt dispersed in the outer layer of the catalyst is Pt atoms or nanoscale Pt atomic clusters.
[0018] According to some specific embodiments of the present invention, the particle size of the nanoscale Pt atomic cluster is greater than 2 nm.
[0019] According to some specific embodiments of the present invention, the Pt dispersion value measured by the hydrogen-oxygen titration method is not less than 85%.
[0020] According to some specific embodiments of the present invention, the Pt dispersion value measured by the hydrogen-oxygen titration method is 85-100%.
[0021] According to some specific embodiments of the present invention, the thickness of the shell layer is 30-70% of the radius of the spherical catalyst particle.
[0022] According to some specific embodiments of the present invention, the radius of the spherical θ-alumina is 0.5-1.2 mm, and the specific surface area is 50-160 m 2 / g, bulk density is 0.5-0.8g / cm 3 .
[0023] According to some specific embodiments of the present invention, the Pt-based dehydrogenation catalyst is prepared by a method comprising the following steps: loading Sn and alkali metal and / or alkaline earth metal components onto a carrier by an impregnation method, drying and then calcining, then loading the Pt component by an impregnation method, and then drying and calcining to obtain the Pt-based dehydrogenation catalyst.
[0024] According to some specific embodiments of the present invention, loading Sn and alkali metal and / or alkaline earth metal components onto the carrier by impregnation includes impregnating the carrier with an aqueous solution of a water-soluble salt of Sn and a water-soluble salt of an alkali metal and / or alkaline earth metal.
[0025] According to some specific embodiments of the present invention, the water-soluble salt of Sn and the water-soluble salt of alkali metal and / or alkaline earth metal respectively and independently include nitrate, sulfate and hydrochloride thereof.
[0026] According to some specific embodiments of the present invention, the calcination temperature after loading Sn and alkali metal and / or alkaline earth metal components is 400-800°C, preferably 400-600°C, and more preferably 500°C.
[0027] According to some specific embodiments of the present invention, the calcination time after loading Sn and alkali metal and / or alkaline earth metal components is 1-10 hours, preferably 2-5 hours.
[0028] According to some specific embodiments of the present invention, loading the Pt component includes using an aqueous solution of chloroplatinic acid as an impregnation solution and loading the Pt component under a pH value of 1-4 (preferably 1-2).
[0029] According to some specific embodiments of the present invention, the calcination temperature after loading the Pt component is 400-800°C, preferably 400-600°C, and more preferably 500°C.
[0030] According to some specific embodiments of the present invention, the calcination time after the Pt component is loaded is 1-10 h, preferably 2-5 h.
[0031] According to some specific embodiments of the present invention, the drying temperature after loading the Pt component is 100-300°C, preferably 120-200°C.
[0032] On the other hand, the present invention also provides the use of the Pt-based dehydrogenation catalyst described in any one of the present invention in the dehydrogenation of low-carbon saturated hydrocarbons to produce low-carbon olefins.
[0033] According to some specific embodiments of the present invention, the low-carbon saturated hydrocarbon is ethane, propane, butane or pentane.
[0034] In summary, the present invention provides a Pt-based dehydrogenation catalyst and its application. The catalyst of the present invention has the following advantages:
[0035] The present invention solves the problem that when conventional propane dehydrogenation propylene production noble metal catalyst is burned and regenerated, the carbon deposits in the center or on the inner core of the catalyst are difficult to be completely burned off, the catalyst is damaged and dust is serious. The catalyst of the present invention is easy to burn and regenerate, and has the advantages of low burning and regeneration temperature and low catalyst damage rate.
[0036] The present invention alleviates the phenomena of reduced strength of the regenerated catalyst, screen clogging, increased pressure drop, decreased reaction performance, etc., thereby enhancing safe operation, improving the start-up cycle, and increasing production efficiency.
[0037] The present invention solves the Cl loss phenomenon on the traditional propane dehydrogenation catalyst and avoids the Cl corrosion problem of the device equipment.
[0038] The catalyst of the present invention is suitable for the reaction of producing propylene by dehydrogenating propane, and has excellent propane conversion rate and propylene yield.
[0039] The catalyst carrier of the invention is simple, low in cost and easy to prepare. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The morphology diagrams show that Pt is evenly and highly dispersedly distributed in the outer layer of the catalyst in Examples 2 to 5, presenting a shell-like shape with a certain thickness.
[0041] Figure 2 The catalyst carrier in Example 1 conforms to the XRD diffraction peak spectrum of θ-alumina.
[0042] Figure 3It is a cross-sectional view of the catalyst in Comparative Examples 1, 2, and 4, wherein Pt is evenly distributed from the outer surface to the inner core.
[0043] Figure 4 This is a typical STEM electron microscope image of the catalyst of the present invention in Example 6. DETAILED DESCRIPTION
[0044] The implementation process of the present invention and the beneficial effects produced are described in detail below through specific embodiments, which is intended to help readers better understand the essence and characteristics of the present invention, and is not intended to limit the scope of implementation of the present invention.
[0045] Example 1
[0046] The shell-type propane dehydrogenation catalyst of this embodiment, such as Figure 1 As shown, it is called catalyst A. First, a commercial carrier is purchased or customized. The carrier is spherical θ-alumina with a radius of 0.5 mm and a specific surface area of 50 m 2 / g, bulk density is 0.5g / cm 3 The diffraction peaks are consistent with Figure 2 The XRD spectrum shown in the figure is as follows; then 0.05wt% Sn and 0.3wt% Na are loaded by impregnation method, the solvent is deionized water, the solutes are Sn(NO3)2 and NaNO3 respectively, and the sample is dried and calcined at 500℃ for 2h; after calcination, the sample is further loaded with 0.1wt% Pt by impregnation method, the solvent is deionized water, the solute is chloroplatinic acid, nitric acid is added to adjust the pH value of the solution to 2, impregnated for 0.2h under normal temperature stirring, then dried at 200℃ and calcined at 500℃ for 2h; at this time, the catalyst metal is in an oxidized state, and if necessary, it can be further reduced in hydrogen to a reduced state. Finally, Pt is uniformly loaded on the outer layer of the catalyst, the thickness of Pt accounts for 10% of the radius, and there is no Pt distribution in the center or core of the catalyst (proof method: after the catalyst is reduced at 500℃ for 2h by hydrogen, the core is white or light-colored, and the outer layer loaded with Pt is gray or dark). The Pt content of the catalyst is 0.1%, the Sn content is 0.05%, the Cl content is 0%, and the Na content is 0.3%. The Pt dispersion value measured by the hydrogen-oxygen titration method is 91%. The microscopic morphology of Pt presents single atoms, diatoms or atomic clusters, such as Figure 4 As shown in the STEM scanning transmission electron microscope photograph, it is in a highly dispersed state.
[0047] Example 2
[0048] The shell-type propane dehydrogenation catalyst of this embodiment, such as Figure 1 As shown, it is called catalyst B. First, a commercial carrier is purchased or customized. The carrier is spherical θ-alumina with a radius of 0.8 mm and a specific surface area of 80 m 2 / g, bulk density is 0.6g / cm 3 The diffraction peaks are consistent with Figure 2 The XRD spectrum shown; then 0.3wt% Sn and 1.2wt% K were loaded by impregnation method, the solvent was deionized water, the solutes were Sn(NO3)2 and KNO3 respectively, and after drying, they were calcined at 500℃ for 3h; after calcination, the sample was further loaded with 0.2wt% Pt by impregnation method, the solvent was deionized water, the solute was chloroplatinic acid, and hydrochloric acid was added to adjust the pH value of the solution to 1.5, and it was impregnated for 0.4h under stirring at room temperature, and then dried at 200℃ and calcined at 500℃ for 3h; at this time, the catalyst metal was in an oxidized state, and if necessary, it could be further reduced in hydrogen to a reduced state. Finally, Pt was evenly loaded on the outer layer of the catalyst, the thickness of Pt accounted for 30% of the radius, and there was no Pt distribution in the center or core of the catalyst (after the catalyst was reduced at 500℃ for 2h in hydrogen, the core was white or light-colored), as shown Figure 1 As shown. The Pt content of the catalyst is 0.2%, the Sn content is 0.3%, the Cl content is 0.1%, and the K content is 1.2%. The Pt dispersion value determined by the hydrogen-oxygen titration method is 96%. The STEM scanning transmission electron microscope photo of Pt and Figure 4 similar.
[0049] Example 3
[0050] The shell-type propane dehydrogenation catalyst of this embodiment, such as Figure 1 As shown, it is called catalyst C. First, a commercial carrier is purchased or customized. The carrier is spherical θ-alumina with a radius of 1.0 mm and a specific surface area of 120 m 2 / g, bulk density is 0.7g / cm 3 The diffraction peaks are consistent with Figure 2 The XRD spectrum shown; then 0.6wt% Sn and 1.2wt% Ca were loaded by impregnation method, the solvent was deionized water, the solutes were Sn(NO3)2 and Ca(NO3)2 respectively, and after drying, they were calcined at 500℃ for 4h; after calcination, the sample was further loaded with 0.4wt% Pt by impregnation method, the solvent was deionized water, the solute was chloroplatinic acid, hydrochloric acid was added to adjust the pH value of the solution to 1.2, and then it was impregnated for 0.6h under stirring at room temperature, then dried at 150℃ and calcined at 500℃ for 4h; at this time, the catalyst metal was in an oxidized state, and if necessary, it could be further reduced in hydrogen to a reduced state. Finally, Pt was evenly loaded on the outer layer of the catalyst (after the catalyst was reduced at 500℃ for 2h, the inner core was white or light-colored), the thickness of Pt accounted for 70% of the radius, and there was no Pt distribution in the center or inner core of the catalyst, such as Figure 1 As shown. The Pt content of the catalyst is 0.4%, the Sn content is 0.6%, the Cl content is 0.4%, and the Ca content is 1.2%. The Pt dispersion value determined by the hydrogen-oxygen titration method is 91%. The STEM scanning transmission electron microscope photo of Pt is Figure 4 similar.
[0051] Example 4
[0052] The shell-type propane dehydrogenation catalyst of this embodiment, such as Figure 1 As shown, it is called catalyst D. First, a commercial carrier is purchased or customized. The carrier is spherical θ-alumina with a radius of 1.2 mm and a specific surface area of 160 m 2 / g, bulk density is 0.8g / cm 3 The diffraction peaks are consistent with Figure 2 The XRD spectrum shown; then 2.0wt% Sn, 2.0wt% Li and 1.0wt% Mg were loaded by impregnation method, the solvent was deionized water, and the solutes were Sn(NO3)2, LiNO3 and Mg(NO3)2 respectively, and then dried and calcined at 500℃ for 5h; after calcination, the sample continued to be loaded with 1.0wt% Pt by impregnation method, the solvent was deionized water, the solute was chloroplatinic acid, and hydrochloric acid was added to adjust the pH value of the solution to 1. It was impregnated for 0.8h under stirring at room temperature, then dried at 120℃ and calcined at 500℃ for 5h; at this time, the catalyst metal was in an oxidized state, and if necessary, it could be further reduced in hydrogen to a reduced state. Finally, the carrier was spherical θ-alumina with a radius of 1.2mm and a specific surface area of 160m 2 / g, bulk density is 0.8g / cm 3 The diffraction peaks are consistent with Figure 2 The XRD spectrum shown in Figure 1 shows that Pt is uniformly loaded on the outer layer of the catalyst (after the catalyst is reduced with hydrogen at 500°C for 2h, the inner core is white or light-colored). The morphology of Pt is thick shell-like, with the thickness accounting for 90% of the radius. There is no Pt distribution in the center or inner core of the catalyst, as shown in Figure 11. Figure 1 As shown. The Pt content of the catalyst is 1.0%, the Sn content is 2.0%, the Cl content is 0.8%, the Li content is 2.0%, the Mg content is 1.0%, and the total content of Li and Mg is 3.0wt%. The Pt dispersion value determined by the hydrogen-oxygen titration method is 90%. The STEM scanning transmission electron microscope photo of Pt and Figure 4 similar.
[0053] Comparative Example 1
[0054] Typical commercial propane dehydrogenation catalyst, referred to as Comparative Agent 1. Pt is evenly distributed inside and outside the alumina. The morphology of Pt on the catalyst is shown in Figure 3 As shown, the catalyst is uniform inside and outside. The catalyst radius is 0.9 mm, the Pt content is 0.4%, the Sn content is 0.4%, and it also contains a certain amount of Cl and auxiliary metals. The Pt dispersion value determined by the hydrogen-oxygen titration method is 90%.
[0055] Comparative Example 2
[0056] A propane dehydrogenation catalyst was prepared according to the Chinese journal article "Effects of Solvents and Competitive Adsorbents on the Performance of PtSnK / γ-Al2O3 Isobutane Dehydrogenation Catalysts", referred to as Comparative Agent 2. Pt is evenly dispersed inside and outside the catalyst, and the morphology of Pt on the catalyst is also shown in Figure 3 As shown, the inside and outside are uniform. The catalyst carrier is γ-alumina, and the metal is loaded by equal volume co-impregnation method, wherein the Pt content is 0.5%, the Sn content is 0.6%, the Cl content is 0.1%, and the K content is 0.8%. The Pt dispersion value determined by the hydrogen-oxygen titration method is 65%.
[0057] Comparative Example 3
[0058] According to the Chinese journal article "Preparation of Eggshell-type Pt / γ-Al2O3 Catalyst and Its Catalytic Combustion Activity for Benzene", a single metal Pt / Al2O3 thin shell catalyst was prepared, called Comparative Agent 3. Pt is only loaded on the very thin outer surface of the catalyst, with a shell thickness of about 15μm, accounting for 0.3% of the catalyst radius. The catalyst carrier is γ-alumina, and the equal volume co-impregnation method is adopted, with ethanol as the impregnation liquid, and the Pt content of the catalyst is 0.29%. The Pt dispersion value determined by the hydrogen-oxygen titration method is 30%.
[0059] Comparative Example 4
[0060] According to the Chinese journal article "Study on the Preparation of Pt / Al2O3 Catalyst by Impregnation Method - Effect of Competitive Adsorbent on Pt Distribution", a single metal Pt / Al2O3 catalyst was prepared, called Comparative Agent 4. The catalyst carrier is η-alumina, and citric acid is used as the competitive adsorbent. Pt is evenly dispersed inside and outside the catalyst. The morphology of Pt on the catalyst is also shown in Figure 3 The catalyst has a Pt content of 0.3%, and the Pt dispersion value is 60% as determined by the hydrogen-oxygen titration method.
[0061] Comparative Example 5
[0062] According to the Chinese journal article "Preparation and TPT Characterization of Pt-Sn / Al2O3 Catalysts with Different Pt Distributions", a bimetallic Pt-Sn / Al2O3 catalyst was prepared, referred to as Comparative Agent 5. The catalyst carrier was γ-alumina, and a competitive adsorbent was used to prepare an eggshell-type catalyst. The catalyst had a Pt content of 0.3%, and the Pt dispersion value was 80% as determined by the hydroxyl titration method.
[0063] Comparative Example 6
[0064] According to the method disclosed in Chinese patent CN201711019192.0, a single Pt thick shell catalyst was prepared, which is called comparative agent 6. The Pt content of the catalyst is 0.7wt%, and the Pt dispersion value is 50% as determined by the hydrogen-oxygen titration method.
[0065] Test Example 1
[0066] The reaction performance of propane dehydrogenation to propylene of each catalyst was evaluated. The raw material was pure propane, the reaction evaluation device was a 20 mL fixed bed evaluation device, the reaction temperature was 580°C, the pressure was normal, and the reaction results of each catalyst were shown in Table 1 below.
[0067] Table 1 Propane dehydrogenation reaction results
[0068]
[0069]
[0070] It can be seen that, compared with the comparative agent, the shell-type catalyst of the present invention has higher propane conversion, propylene selectivity and propylene yield.
[0071] Analysis of the catalysts after the reaction revealed that the Cl contents of the comparative agents 1, 3, and 5 were all 0.1 to 0.2 wt% lower than those before the reaction, indicating that the Cl element on the comparative agent catalysts was significantly lost; while the Cl contents of the catalysts A, B, C, and D of the present invention remained unchanged before and after the reaction, and no Cl element loss was found.
[0072] Test Example 1
[0073] At normal pressure, nitrogen atmosphere, oxygen content of 1 mol%, and temperature of 500°C, the charring performance of the catalysts after the above reactions was investigated. The charring state is shown in Table 2 below.
[0074] Table 2 The state of carbon deposited catalyst after burning
[0075] catalyst Burnt state Contrast agent 1 There is carbon deposit in the core that has not been burned out, and 0.2-1% of the catalysts are cracked. Contrast agent 2 There is carbon deposit in the core that has not been burned out, and 0.2-1% of the catalysts are cracked. Contrast agent 3 All burned cleanly, no catalyst cracking Contrast agent 4 There is carbon deposit in the core that has not been burned out, and 0.2-1% of the catalysts are cracked. Contrast agent 5 All burned cleanly, no catalyst cracking Contrast agent 6 All burned cleanly, no catalyst cracking Catalyst A All burned cleanly, no catalyst cracking Catalyst B All burned cleanly, no catalyst cracking Catalyst C All burned cleanly, no catalyst cracking Catalyst D All burned cleanly, no catalyst cracking
[0076] Criteria for judging whether the carbon on the catalyst is burned clean: After the catalyst is cut open, if the inner core or the center is obviously darker than the surrounding area, it means that the carbon is not completely burned; if the inside and outside of the catalyst are white or light-colored, and the color is uniform, it means that the catalyst is completely burned clean.
[0077] It can be seen that compared with the contrast agent with Pt evenly dispersed inside and outside, the carbon deposits produced by the shell-type catalyst of the present invention are easier to burn, all the carbon deposits are burned off, and no catalyst cracking occurs, and no obvious dust is generated. For the production process of continuous catalyst regeneration, the catalyst prepared by the present invention, while ensuring sufficiently high reaction performance, has the characteristic of being easier to burn, which not only makes the burning temperature lower, thereby reducing catalyst wear and device energy consumption, but also can fully ensure that the catalyst is burned and regenerated more thoroughly, thereby ensuring the best recovery of catalyst activity.
Claims
1. A Pt-based dehydrogenation catalyst, wherein: The Pt-based dehydrogenation catalyst uses spherical θ-alumina as a carrier, the active component Pt is completely dispersed in the outer layer of the catalyst to form spherical catalyst particles, and the active component Pt forms a shell layer; based on the total mass of the Pt-based dehydrogenation catalyst as 100%, the Pt content is 0.1-1.0wt%, the thickness of the shell layer is 30-70% of the radius of the spherical catalyst particle, the radius of the spherical θ-alumina is 0.5-1.2mm, and the specific surface area is 50-160m 2 / g, bulk density is 0.5-0.8g / cm 3 The Pt-based dehydrogenation catalyst is prepared by the following steps: loading Sn and alkali metal and / or alkaline earth metal components onto a carrier by an impregnation method, drying and calcining, then loading Pt component by an impregnation method, and then drying and calcining to obtain the Pt-based dehydrogenation catalyst; the calcination temperature after loading Sn and alkali metal and / or alkaline earth metal components is 400-800°C; the calcination temperature after loading Pt component is 400-800°C; loading Sn and alkali metal and / or alkaline earth metal components onto a carrier by an impregnation method is to impregnate the carrier with a water-soluble salt of Sn and an aqueous solution of a water-soluble salt of alkali metal and / or alkaline earth metal; loading Pt component is to use an aqueous solution of chloroplatinic acid as an impregnation solution, and load it under the condition of pH value of 1-2.
2. The Pt-based dehydrogenation catalyst according to claim 1, wherein Taking the total mass of the Pt-based dehydrogenation catalyst as 100%, the Pt content is 0.2-0.4wt%.
3. The Pt-based dehydrogenation catalyst according to claim 1, wherein Taking the total mass of the Pt-based dehydrogenation catalyst as 100%, the Pt-based dehydrogenation catalyst further contains the following percentage components: 0.05-2.0 wt% of Sn, 0-0.8 wt% of Cl, and 0.3-3.0 wt% of at least one alkali metal and / or alkaline earth metal.
4. The Pt-based dehydrogenation catalyst according to claim 1, wherein The Pt dispersed in the outer layer of the catalyst is Pt atoms or nanoscale Pt atomic clusters.
5. The Pt-based dehydrogenation catalyst according to claim 1, wherein The Pt dispersion value determined by the hydroxyl titration method is 85-100%.
6. The Pt-based dehydrogenation catalyst according to claim 1, wherein The water-soluble salts of Sn and the water-soluble salts of alkali metals and / or alkaline earth metals include independently their nitrates, sulfates and hydrochlorides.
7. The Pt-based dehydrogenation catalyst according to claim 1, wherein The calcination temperature after loading Sn and alkali metal and / or alkaline earth metal components is 400-600°C.
8. The Pt-based dehydrogenation catalyst according to claim 1, wherein The calcination time after loading Sn and alkali metal and / or alkaline earth metal components is 1-10 hours.
9. The Pt-based dehydrogenation catalyst according to claim 1, wherein The calcination time after loading Sn and alkali metal and / or alkaline earth metal components is 2-5 hours.
10. The Pt-based dehydrogenation catalyst according to claim 1, wherein The calcination temperature after loading the Pt component is 400-600°C.
11. The Pt-based dehydrogenation catalyst according to claim 1, wherein The calcination time after loading the Pt component is 1-10h.
12. The Pt-based dehydrogenation catalyst according to claim 1, wherein The calcination time after loading the Pt component is 2-5h.
13. Use of the Pt-based dehydrogenation catalyst according to any one of claims 1 to 12 in the dehydrogenation of light saturated hydrocarbons to light olefins.
14. The use according to claim 13, wherein: The low carbon saturated hydrocarbon is ethane, propane, butane or pentane.
Citation Information
Patent Citations
High-efficiency catalyst for producing chloroform by gas phase hydrogenation of carbon tetrachloride
CN107876046A
Catalyst for dehydrogenation of low hydrocarbons and preparation method thereof
CN111097457A